Percutaneous Instrumentation Without Arthrodesis for Thoracolumbar Flexion-Distraction Injuries: A Review of the Literature. Issue 2 (27th December 2016) - Chu, Jason K.; Rindler, Rima S.; Pradilla, Gustavo; Rodts, Gerald E.; Ahmad, Faiz U.
Abstract: BACKGROUND: Flexion-distraction injuries (FDI) represent 5% to 15% of traumatic thoracolumbar fractures. Treatment depends on the extent of ligamentous involvement: osseous/Magerl type B2 injuries can be managed conservatively, while ligamentous/Magerl type B1 injuries undergo stabilization with arthrodesis. Minimally invasive surgery without arthrodesis can achieve similar outcomes to open procedures. This has been studied for burst fractures; however, its role in FDI is unclear. OBJECTIVE: To conduct a systematic review of the literature that examined minimally invasive surgery instrumentation without arthrodesis for traumatic FDI of the thoracolumbar spine. METHODS: Four electronic databases were searched, and articles were screened using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines for patients with traumatic FDI of the thoracolumbar spine treated with percutaneous techniques without arthrodesis and had postoperative follow-up. RESULTS: Seven studies with 44 patients met inclusion criteria. There were 19 patients with osseous FDI and 25 with ligamentous FDI. When reported, patients (n = 39) were neurologically intact preoperatively and at follow-up. Osseous FDI patients underwent instrumentation at 2 levels, while ligamentous injuries at approximately 4 levels. Complication rate was 2.3%. All patients had at least 6 mo of follow-up and demonstrated healing on follow-up imaging. CONCLUSION: Percutaneous instrumentation without arthrodesis represents a low-risk intermediate between conservative management and open instrumented fusion. This "internal bracing" can be used in osseous and ligamentous FDIs. Neurologically intact patients who do not require decompression and those that may not tolerate or fail conservative management may be candidates. The current level of evidence cannot provide official recommendations and future studies are required to investigate long-term safety and efficacy.